2013
DOI: 10.1093/carcin/bgt395
|View full text |Cite
|
Sign up to set email alerts
|

Cancerous inhibitor of PP2A is targeted by natural compound celastrol for degradation in non-small-cell lung cancer

Abstract: Celastrol binds CIP2A and enhances CIP2A-CHIP interaction, leading to ubiquitination/degradation of CIP2A and inhibition of lung cancer cells in vitro and in vivo. Celastrol potentiates cisplatin's efficacy by suppressing the CIP2A-Akt pathway, and therefore CIP2A inhibitors may represent novel therapeutics for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 53 publications
3
89
0
Order By: Relevance
“…In addition, the invasive behavior of MDA-MB-231 cells was examined by CIP2A small interfering (si)siRNA, and found that CIP2A depletion inhibits the invasion and migration of MDA-MB-231. Previously, CIP2A has been shown to be an oncoprotein capable of modulating phosphorylated-Akt (pAkt) (9,12). Results of the present study demonstrated that CIP2A depletion inhibits phosphorylation of Akt and its downstream molecules, mechanistic target of rapamycin (mTOR) and p70 ribosomal protein S6 kinase (P70S6K).…”
Section: Introductionmentioning
confidence: 47%
See 3 more Smart Citations
“…In addition, the invasive behavior of MDA-MB-231 cells was examined by CIP2A small interfering (si)siRNA, and found that CIP2A depletion inhibits the invasion and migration of MDA-MB-231. Previously, CIP2A has been shown to be an oncoprotein capable of modulating phosphorylated-Akt (pAkt) (9,12). Results of the present study demonstrated that CIP2A depletion inhibits phosphorylation of Akt and its downstream molecules, mechanistic target of rapamycin (mTOR) and p70 ribosomal protein S6 kinase (P70S6K).…”
Section: Introductionmentioning
confidence: 47%
“…Recently, CIP2A expression has been found to be associated with the invasive function of breast cancer (10). Based on the role of CIP2A in stabilizing and upregulating the c-Myc oncoprotein, previous reports found that c-Myc is involved in CIP2A-stimulated invasiveness of tumor cells (3,9,10). The expression of c-Myc was analyzed by western blot, and it was observed that c-Myc is downregulated by CIP2A depletion.…”
Section: A B C Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These compounds had the following IC 50 values in FPPS inhibition: compound 9:, TbFPPS, 17 μM and HsFPPS, no activity; compound 10: TbFPPS, 54 μM; HsFPPS, 81 μM (SI Appendix, Table S1). Both compounds are quinone methides, and compound 9 has diverse biological activities (30)(31)(32)(33). Therefore we elected to use compound 9 as the basis for a similarity search using the NCI/ DTP option in PubChem (https://pubchem.ncbi.nlm.nih.gov/) with compounds again being obtained from the NCI/DTP (http://dtp.…”
Section: Resultsmentioning
confidence: 99%